Patriot – new variety of vegetable pieas - A. G. Besedin; A. V. Tikhonova; O. V. Putina (Овощи России, 2021)
Relevance. The purpose of the research was to produce a new medium-ripe, high-yielding variety of vegetable peas with the usual type of leaf to expand the variety in the now used conveyor variety selection of the Krymsk EBS VIR Branch.Materials and methods. The experience was laid on the fields of the Krymsk EBS VIR Branch (Russia, Krasnodar Region, Krymsk) in 2019-2020. Varieties and strain were evaluated in a competitive variety testing. Sowing was carried out with a selection seeder SKS-6-10. The plot area was 10 m2 , the experiment was repeated four times. In the phase of technical ripeness, the sheaves were selected for description and the yield was taken into account. The conservation of green peas was done at the Tech Evaluation Lab.Results. Competitive variety testing in the mid-ripeness group was held by two strains 2014/7 and 344/16. The strain 2014/17 for green pea yields surpassed the standard "Parus" and G-344/16 in both years of study. Fresh and processed green peas were rated by the Tasting Commission at 5.0 and 4.8 points, respectively. High yield is achieved due to the paired beans on the peduncle and a large number of grains in the bean, up to 10 pieces. The grain in technical ripeness has a dark green color and the linear dimensions are 9.0x8.1 mm. In biological maturity, the seeds are intensely green, angular-compressed with a mass of 1000 pieces. 188-225 g.Conclusion. The results of field and laboratory analyses carried out on the complex of economicvaluable characteristics made it possible to distinguish the strain 2014/7, which in 2020 was transferred to the State Variety Testing under the name "Patriot". It is recommended as a supplement to the existing set of vegetable pea varieties of the Krymsk EBS VIR Branch in the mid-ripe group.